2009
DOI: 10.1111/j.1549-0831.2009.tb00703.x
|View full text |Cite
|
Sign up to set email alerts
|

Consumer Trust in the U.S. Food System: An Examination of the Recreancy Theorem*

Abstract: Because consumer opinions to an increasing extent affect the structure and management of the U.S. food system, it is important for social scientists to accurately model consumer trust in this system so they can better understand and anticipate public responses to existing or proposed food‐related regulatory policies and facilitate effective partnership building between food‐system representatives and the public. The recreancy theorem posits that individuals' trust in and support for societal institutions refle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
54
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(62 citation statements)
references
References 36 publications
6
54
0
2
Order By: Relevance
“…For both samples, we selected individuals to ensure male and female household members would be alternately represented. Response rates are similar to recent surveys of food and environmental attitudes, which researchers note have been declining over time (Dietz, Dan, and Shwom 2007;Ohlendorf et al 2002;Sapp et al 2009).…”
Section: Methodssupporting
confidence: 80%
“…For both samples, we selected individuals to ensure male and female household members would be alternately represented. Response rates are similar to recent surveys of food and environmental attitudes, which researchers note have been declining over time (Dietz, Dan, and Shwom 2007;Ohlendorf et al 2002;Sapp et al 2009).…”
Section: Methodssupporting
confidence: 80%
“…Demand for dairy products is driven by consumer desire for inexpensive food that is safe, high quality, and produced using socially responsible management practices (Rollin, 2004;Fulwider et al, 2008;Sapp et al, 2009). Bulk milk somatic cell count (BMSCC) and total bacterial count (BMTBC) are international reference indicators of raw milk quality (Costello et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…political party affiliation, political ideology) characteristics did. Sapp et al (2009) found that confidence and fiduciary responsibility explained approximately 70% of the variance in consumer trust in institutional actors within the US food system, wherein the effects of fiduciary responsibility outweighed the effects of confidence on trust by a factor of about three to one.…”
Section: The Recreancy Theoremmentioning
confidence: 98%